Determinants of Patient Loyalty in a Regional Hospital: The Impact of Satisfaction, Image, and Trust - Ep Lubis, Asyifa Zulinanda; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (Hasanuddin Medan, 2024)
This study examines the key factors influencing patient loyalty at RSU Dr. R.M. Djoelham Binjai, focusing on patient satisfaction, hospital image, and trust. The purpose is to determine how these factors impact patients' intentions to return for future healthcare services. A quantitative research design was employed, using a cross-sectional analytical survey conducted on 93 inpatients from Super VIP, VIP, and Class 1 rooms. Data were collected through structured questionnaires and analysed using univariate, bivariate, and multivariate methods to explore the relationships between satisfaction, image, trust, and revisit intentions. The results demonstrate that higher patient satisfaction significantly increases the likelihood of returning to the hospital. A positive hospital image also plays a crucial role in fostering patient trust, which further enhances revisit intentions. The multivariate analysis confirms that patient satisfaction is the most significant predictor of loyalty, followed closely by trust and hospital image. In conclusion, the study highlights the importance of maintaining high service quality, a positive hospital image, and strong patient trust to enhance patient loyalty. Hospital management should focus on these areas to improve patient retention and ensure ongoing patronage.